Audio-Vestibular Findings in Patients with Hyperuricemia - Mohamed Mahmoud Al-Sobki (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Hyperuricemiais a common biochemical disturbance in which serum concentration of uric acid exceeds the normal values which is 7.0 mg/dl in men and more than 6.0 mg/dl in women leading to deposition of monosodium urate [MSU] crystals in joints and soft tissues resulting in inner ear functions affection. Aim of the work: To elaborate the effect of hyperuricemia on the peripheral hearing as well as peripheral vestibular functions. Subjects and Methods: This study included 40 subjects with hyperuricemia and 40 healthy controls. Participants underwent serum uric acid assay, full history taking, basic audiological evaluation and vestibular evaluation. Results: 37[92.5%] hyperuricemic subjects had normal peripheral hearing sensitivity, only 3[7.5%] had mild high frequencies sensori-neural hearing loss [SNHL] at 8 kHz. 31[77.5%] Hyperuricemic patients had normal peripheral vestibular functions, only 9[22.5%] subjects had BPPV; They also had higher serum uric acid [SUA] level. No correlation between duration of hyperuricemia and occurrence of BPPV. Conclusions: The hyperuricemic subjects had a significant higher incidence of BPPV. Other investigations to detect early and subtle changes in cochlear function of hyperuricemic subjects were recommended.